2020
DOI: 10.1016/j.addbeh.2019.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Time invariance of three ultra-brief internet-related instruments: Smartphone Application-Based Addiction Scale (SABAS), Bergen Social Media Addiction Scale (BSMAS), and the nine-item Internet Gaming Disorder Scale- Short Form (IGDS-SF9) (Study Part B)

Abstract: Time invariance of three ultra-brief internet-related instruments: Smartphone Application-Based Addiction Scale (SABAS), Bergen Social Media Addiction Scale (BSMAS), and the nine-item Internet Gaming Disorder Scale-Short Form (IGDS-SF9)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
108
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 51 publications
(40 reference statements)
22
108
0
6
Order By: Relevance
“…BSMAS scores correlated with IGDS9-SF scores and assessments of anxiety and depression [34]. The BSMAS has been previously validated among Hong Kong participants [45,46]. The internal consistency of the BSMAS in the present study was 0.83.…”
Section: The Bergen Social Media Addiction Scale (Bsmas)supporting
confidence: 52%
See 1 more Smart Citation
“…BSMAS scores correlated with IGDS9-SF scores and assessments of anxiety and depression [34]. The BSMAS has been previously validated among Hong Kong participants [45,46]. The internal consistency of the BSMAS in the present study was 0.83.…”
Section: The Bergen Social Media Addiction Scale (Bsmas)supporting
confidence: 52%
“…The IGDS9-SF has demonstrated high internal consistency (α = 0.87) and low floor or ceiling effects [44]. The IGDS9-SF has also been validated among Hong Kong participants [45,46]. The internal consistency of the IGDS9-SF in the present study was 0.91.…”
Section: Internet Gaming Disorder Scale-short Form (Igds9-sf)supporting
confidence: 50%
“…The psychometric properties of the BSMAS and Chinese BSMAS have been found to be satisfactory. [25][26][27][28] The present study also showed that the Chinese BSMAS had good internal consistency (α = 0.88). anxiety or even sadness when you try to either reduce or stop your gaming activity?"…”
Section: Bergen Social Media Addiction Scale (Bsmas)supporting
confidence: 51%
“…The BSMAS has shown good validity and reliability in previous research (Andreassen et al 2016;Andreassen et al 2017;Bányai et al 2017;Lin et al 2017;Monacis et al 2017). The scale has shown measurement invariance across two Chinese cultural areas (Leung et al 2020), as well as time invariance (Chen et al 2020). In the present study the Cronbach's alpha reliability coefficient was .77.…”
Section: Instrumentssupporting
confidence: 51%
“…While the names "Bergen Social Media Addiction Scale" and "Bergen Social Networking Addiction Scale" are used interchangeably in the literature (Andreassen et al 2017;Andreassen et al 2017), we use in the following "social networking sites" as social media and social networking sites reflect similar but yet distinct phenomena (see Kuss and Griffiths 2017). The psychometric robustness of the BSMAS has been examined in Italian (Monacis et al 2017), Hungarian (Bányai et al 2017), Persian (Lin et al 2017), and Chinese (Leung et al 2020;Chen et al 2020) samples, where it has showed good properties. Although previous studies have used a variety of methods to examine this scale, there is currently no study that has investigated the psychometric properties of the BSMAS in comparison to the BFAS.…”
Section: Bergen Social Media Addiction Scale and Bergen Facebook Addimentioning
confidence: 99%